2017
DOI: 10.3389/fpsyg.2017.01090
|View full text |Cite
|
Sign up to set email alerts
|

Mandarin-Speaking Children’s Speech Recognition: Developmental Changes in the Influences of Semantic Context and F0 Contours

Abstract: The goal of this developmental speech perception study was to assess whether and how age group modulated the influences of high-level semantic context and low-level fundamental frequency (F0) contours on the recognition of Mandarin speech by elementary and middle-school-aged children in quiet and interference backgrounds. The results revealed different patterns for semantic and F0 information. One the one hand, age group modulated significantly the use of F0 contours, indicating that elementary school children… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…The speech materials were used in our previous studies with native Japanese speakers learning Chinese as a foreign language ( Zhang et al, 2016 ) and Chinese school-age children ( Zhou et al, 2017 ). Cronbach’s alpha values ranged from 0.81 to 0.89 for different types of stimuli in all the studies including the present one, reflecting high internal consistency of each type of stimuli.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The speech materials were used in our previous studies with native Japanese speakers learning Chinese as a foreign language ( Zhang et al, 2016 ) and Chinese school-age children ( Zhou et al, 2017 ). Cronbach’s alpha values ranged from 0.81 to 0.89 for different types of stimuli in all the studies including the present one, reflecting high internal consistency of each type of stimuli.…”
Section: Methodsmentioning
confidence: 99%
“…The experimental protocol followed our previous studies ( Wang et al, 2013 ; Zhou et al, 2017 ). In a quiet room with ambient noise level no higher than 15 dB sound pressure level, children listened to the stimuli and were required to report orally what they heard.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…By contrast, children aged 8-10 years required shorter portions of the target words (i.e., less acoustic-phonetic information) for recognition in high-predictability than in low-predictability sentences (Craig et al, 1993). Our previous study (Zhou et al, 2017) showed that elementary school children aged 10 years could not make better use of semantic context in recognizing speech with flattened fundamental frequency (F0) contours compared to speech with natural F0 contours. By contrast, middle school children aged 14 years benefited more from semantic context when natural F0 contours were altered regardless of whether the spoken sentences were presented in quiet or suboptimal listening backgrounds.…”
Section: Introductionmentioning
confidence: 94%
“…Specifically, to assess the role of contextual semantic integration in speech recognition, we introduced acoustic manipulations in two speech-in-noise conditions, one with natural F0 contours kept in the target sentences presented against interfering background speech and the other with flattened F0 contour that disrupted the critical cue for Chinese lexical tones for proper word recognition. This speech-in-noise test protocol with Mandarin Chinese materials had been previously adopted in a number of studies on elementary school students, middle school students, and adults including the elderly population (Wang et al, 2013;Jiang et al, 2017;Zhou et al, 2017), and the results demonstrated that greater auditory semantic integration at the sentence level is required to recognize the words in the F0-degraded condition. Furthermore, two statistical models, i.e., the multiplicative model (product of the two subskills) and additive model (sum of the two subskills), were tested to clarify how the subskills would predict the variance in reading comprehension.…”
Section: Introductionmentioning
confidence: 99%